PANIC DISORDER AS A DETERMINANT OF HYPERTENSION DEVELOPMENT: AUTONOMIC, NEUROBIOLOGICAL, AND BIOPSYCHOSOCIAL MECHANISMS LINKING ACUTE PANIC TO CHRONIC CARDIOVASCULAR DISEASE – REVIEW - Kwiecień, Iga Maria; Bartoszewska, Karolina; Ługowski, Wojciech; Ługowska, Julia; Komorowski - Roszkiewicz, Jakub; Marcyś, Karol; Głowacz, Julia; Nagrodzka, Anna; Matwiejuk, Weronika (International Journal of Innovative Technologies in Social Science, 2026)
Hypertension remains one of the leading global causes of cardiovascular morbidity and mortality. While traditional biomedical risk factors account for substantial risk, increasing evidence suggests that psychological and neurobiological mechanisms contribute significantly to long-term blood pressure regulation. Panic disorder, characterised by recurrent episodes of intense autonomic activation, may represent an under-recognised determinant of sustained hypertension development. This review synthesises epidemiological, autonomic, neurophysiological, inflammatory, and biopsychosocial evidence linking panic disorder with hypertension. Converging evidence indicates altered sympathetic firing patterns, enhanced baroreflex gain, increased blood pressure variability, recurrent hypertensive surges, endothelial dysfunction, and cumulative allostatic load. Longitudinal data demonstrate elevated risk of incident hypertension among individuals with panic disorder independent of conventional cardiovascular risk factors. Integrating mental health assessment into cardiovascular prevention strategies may provide an innovative interdisciplinary approach to reducing global disease burden.